Previous answerer has an error. It should go like this:
2*(2^x)^2 = 3*(2^x) - 1.......(1)
Make temporary substitute
y = 2^x..........(2).
Then (1) becomes:
2*y^2 - 3*y + 1 = 0, which has two real roots:
y1 = (3 + 1)/4 = 1, and
y2 = (3 - 1)/4 = 1/2.
Coming back to (2) you get:
2^x1 = 1 => x1 = 0, and
2^x2 = 2^(-1) => x2 = -1.
Inverting (2) you can use x*ln(2) = ln(y), however it is obvious even without it.
2007-04-18 12:23:20
·
answer #1
·
answered by fernando_007 6
·
0⤊
0⤋
Usually you can use logs to bring down expressions from the exponents, but in this case it's tricky because here you still have that "-1" term you can't really get rid of. So try this instead:
2^(2x+1) = 3(2^x) - 1
2^(2x) * 2 = 3(2^x) - 1
2 * (2^(x))^2= 3(2^x) - 1
2(2^(x))^2 - 3(2^x) + 1 = 0
Let p = 2^(x). Then this becomes
2p^2 - 3p + 1 = 0
(2p - 1)(p - 1) = 0
So p =1/2 or p = 1
this means x = -1 or x = 0
2007-04-18 11:58:34
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2^2x *2 =3*2^x-1
If you call 2^x=z you have
2 z^2-3z+1=0
z=((3+-sqrt(9-8))/4 so z=1 and z= 1/2
2^x =1 so x= 0
and 2^x=1/2 so x=-1
2007-04-18 11:54:20
·
answer #3
·
answered by santmann2002 7
·
0⤊
0⤋
a million. discover via trial and blunder 2. 3 Equations and 3 unknowns remedy one equation for variable, substitute into yet another and remedy the third. you should discover ways to do your individual artwork, solutions do you no reliable, in case you do no longer understand a thank you to derive them
2016-12-26 14:01:39
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2 * 2^x = 3 * 2^x -1
so 2^x = 1
so x = 0
2007-04-18 11:52:36
·
answer #5
·
answered by hustolemyname 6
·
0⤊
0⤋